OUR PROSPECTIVE MATHEMATIC TEACHERS ARE NOT CRITICAL THINKERS YET - Abdur Rahman As'ari; Ali Mahmudi; Elah Nuerlaelah (Journal on Mathematics Education, 2017)
In order to help students develop their critical thinking skills, teachers need to model the critical thinking skills and dispositions in front of their students. Unfortunately, very rare studies investigating prospective teachers’ readiness in critical thinking dispositions are available in the field of mathematics education. This study was intended to investigate the level of critical thinking disposition of prospective mathematics teachers. Using case study methods, three studies were done in Malang.Three levels of critical thinkers were identified from these case studies namely: non-critical thinker, emergent critical thinker, developing critical thinker. Majority of prospective mathematics teachers’ critical thinking dispositions are at the non-critical thinker level. Only a few of them are at the emergent critical thinker, and very rare at the developing critical thinker level. It can be concluded that prospective mathematics teachers are not critical thinker yet. Teacher education institutions need to reform their curriculum and instructional practices to improve their students critical thinking skills and dispositions.DOI: http://dx.doi.org/10.22342/jme.8.2.3961.145-156